Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, Terhadap Nilai Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi(Studi pada Perusahaan Infrastruktur yang terdaftar di Bursa Efek Indonesia Periode 2022 – 2024) - Bintang Saputra; Mardi; Dwi Handarini (Teewan Journal Solutions, 2025)
This study aims to analyze the effect of investment decisions, funding decisions, and dividend policy on firm value, with firm size as a moderating variable. The object of this research is infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Firm value is measured using the Price to Book Value (PBV), while investment decisions are proxied by the Price Earnings Ratio (PER), funding decisions by the Debt to Equity Ratio (DER), dividend policy by the Dividend Payout Ratio (DPR), and firm size by the natural logarithm of total assets. The population consists of 69 infrastructure companies, with a sample of 20 companies selected through purposive sampling over three years of observation, resulting in a total of 60 data points. Data were analyzed using multiple linear regression (MLR) and moderated regression analysis (MRA) with Eviews version 12. The results of the study show that investment decisions and funding decisions have a positive and significant effect on firm value, while dividend policy has a negative and significant effect on firm value. However, firm size is not able to moderate the relationship between investment decisions, funding decisions, and dividend policy on firm value. These findings support signaling theory and provide practical implications for financial managers and investors in making strategic decisions to enhance firm value.